PENGARUH DELEGASI, OTORITAS, TANGGUNG JAWAB TERHADAP KINERJA PEGAWAI - Yolanda Oktarina; Hafidz Aima; Lusiana Lusiana; Silvia Sari; Rafnelly Rafk; Nofriadi Nofriadi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
Employee performance plays an important role in the success and sustainability of the company. Effective management of employees is the key to achieving organizational goals, and factors affecting employee performance have become a major concern in human resource management. Although many studies have been conducted with respect to these factors, there are variations in results and findings. And those who study the factors of delegation, authority and responsibility for employee performance have not been many. So the title of this study is to study the Influence of Delegation, Authority, Responsibility on Employee Performance. This study uses a survey method of a sample of employees from various levels of hierarchy in Agency